Beliefs, Understanding, and Barriers Related to Dementia Research Participation Among Older African Americans. (3rd January 2022) - Pugh, Erika; Stewart, Joshua; Carter, Leah; Calamia, Matthew; Carmichael, Owen; Newton, Robert L.
Abstract : Background: United States Census Bureau projects African Americans (AAs) will be one of the fastest growing populations over the next 30 years. Research suggests they are at higher risk for developing dementia. It is important to know about AA adults' beliefs about, and knowledge of, dementia; and how these beliefs and knowledge impact participation in dementia research. Methods: Four focus groups were completed with 51 older AA adults (76.5% female; mean age=68) in Baton Rouge, Louisiana to examine understanding of dementia and barriers influencing willingness to participate in a clinical trial on dementia risk reduction. Findings: Participants exhibited awareness of several risk and protective factors related to dementia, including family history of dementia, lack of cognitive engagement, and sedentary lifestyles. They were willing to participate in interventions to lower the risk of developing dementia. Barriers to participation included invasive procedures, pharmaceutical interventions, mistrust of investigators, inadequate compensation, and long study duration. Discussion: Given the high relevance of dementia research to older AAs, their knowledge of dementia, and their willingness to participate in dementia research once barriers are addressed, it is imperative to continue to identify and remediate factors contributing to the poor representation of AAs in dementia research.